Ciudad, derecho e imaginario una construcción de lo publico en la convivencia (2014)
The urban crisis dynamically observed from the new century involves rethinking models and concepts aimed at coexistence practices, designed to provide the community with basic tools that allow the proper development of dialogue, mediation and respect for the rules. Thus coexistence becomes possible to build collectively a city, inclusive and equitable that each individual assumes the rights and responsibilities grounded in the rules of coexistence. Living in public space is an option of coexistence, is one of the ways to achieve the recognition of others, respect for difference within social relations. Public space becomes an everyday scenario in which subjects have to incline the proper use of rules, rights and obligations that transcend and embody the sense of belonging and identity to the city, which supports not only the structure of the state but responsibility for all offering opportunities for discussion and consensus, where everyone can meet and freely express their ideas, that's when the public space becomes accessible to the entire community projection